PELATIHAN BIPA BAGI MAHASISWA ASING DALAM MEMBACA TEKS PROSEDUR BERTEMA KULINER PEKALONGAN - Inayatul Ulya (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
Cultured-based BIPA training with a Pekalongan culinary theme aimed to introduce and preserve local culture while teaching foreign students (Nigerian, Thai, and Cambodian) how to read Indonesian procedure text that focused on Pekalongan culinary. This activity combines learning Indonesian language and culture through culinary delights, as an interesting means to understand the social aspects of Indonesian society. This community service used a blended learning method, combining offline and online learning to improve foreign students’ understanding in reading procedure text and identifying information related to Pekalongan culinary delights. Activities begin with preparation of materials and equipment, followed by implementation through online sessions and offline cultural visits. In online sessions, students learn the basics of Indonesian, vocabulary and sentence structures used in procedure text, as well the process of making typical Pekalongan culinary delights such as Tauto. Offline activities include visits to Pekalongan cultural places, such as the Unikal Batik Gallery, Batik Museum, Limun Oriental, Garang Asem Masduki, and Po An Thien Temple. This activity lasted for one month and ended with evaluation and feedback from presenters. The results of this training show that the blended learning approach is efefctive in facilitating foreign students’ understnading of procedure text and introducing Pekalongan culinary and culture as a whole.